Association of specific meniscal pathologies and other structural pathologies with self-reported mechanical symptoms: A cross-sectional study of 566 patients undergoing meniscal surgery. Issue 2 (February 2019) - Pihl, Kenneth; Turkiewicz, Aleksandra; Englund, Martin; Lohmander, L. Stefan; Jørgensen, Uffe; Nissen, Nis; Schjerning, Jeppe; Thorlund, Jonas B.
Abstract: Objectives: We explored associations between specific meniscal pathologies and other concurrent structural knee pathologies with presence of self-reported mechanical symptoms in patients undergoing meniscal surgery. Design: Cross-sectional study. Methods: We included patients undergoing surgery for a meniscal tear from Knee Arthroscopy Cohort Southern Denmark (KACS). Pre-surgery, patients completed online questionnaires including self-reported presence of mechanical symptoms. At arthroscopy, surgeons recorded information about specific meniscal pathologies and other concurrent structural knee pathologies. Relative risks (RR) were estimated to assess associations between specific meniscal pathologies and other structural knee pathologies with preoperative mechanical symptoms from multivariable logistic regression. Results: 566 of 641 patients (mean age 48.6[SD 12.9] years, 57% men) with complete data were included. 386 (68%) patients reported mechanical symptoms of knee catching/locking and/or extension deficit. Most evaluated joint pathologies were not associated with mechanical symptoms of any kind with RRs close to 1.0. Meniscal tears involving both the posterior and anterior horn (n = 22) were associated with knee catching/locking (RR: 1.49[95%CI:1.15–1.93]), and a tear in both menisci (n = 49) was associated with extension deficit of the knee (RR: 1.32[95%CI:1.01–1.73]). A partial (n = 29) and total ACL rupture (n = 37) were each associated with extension deficit (RR: 1.83[95%CI:1.47–2.28] and RR: 1.44[95%CI:1.05–1.98], respectively). Conclusions: Limited associations between specific meniscal pathology and other concurrent knee joint pathologies with presence of self-reported mechanical symptoms were found in patients undergoing meniscal surgery. The findings question the clinical importance of mechanical symptoms as an indicator for arthroscopy for specific meniscal tears with the specific aim to relieve such symptoms.